Sports and Justice in Indonesia: Examining Gender Equality and Fairness in Athletic Opportunities (Indonesian Sports Justice Review, 2024)
Gender inequality remains a persistent challenge in Indonesia’s sports sector, where women face barriers to equal access, representation, and recognition in athletics. This paper explores the state of gender equality in Indonesian sports, critically assessing the policies and societal norms that contribute to the marginalization of female athletes. By analyzing government initiatives, sports federations, and media representations of female athletes, this study identifies the key structural obstacles that hinder women's participation in sports at various levels. Interviews with athletes, coaches, and policy-makers, alongside a review of gender equity frameworks in sports governance, form the basis of this research. The paper argues that achieving gender justice in sports requires not only policy reforms but also a cultural shift towards valuing female athleticism and providing equal opportunities for both genders in training, competition, and leadership roles. Recommendations for addressing gender disparities in Indonesian sports include enhanced funding for women's sports programs, equitable media coverage, and stronger legal protections against discrimination.